Passing Performances Queer Readings of Leading Players in American Theater History - Schanke, Robert Anders; Marra, Kim (University of Michigan Press, 1998)
Passing Performances gathers a range of critical and biographical essays on notable personalities whose major contributions to the stage occurred before 1969, the year of the Stonewall riots that kicked off the gay rights movement in the United States. How these theater practitioners variously "passed"-i.e., managed unconventional sexual inclinations both on- and offstage-significantly determined the course of their personal and professional lives and thus the course of U.S. theater history. The actors, directors, producers, and agents examined here include Edwin Forrest, Charlotte Cushman, and Adah Isaacs Menken, whose personal lives and careers traded on the same-sex erotics of "true love" in the antebellum period; Elisabeth Marbury, Elsie de Wolfe, Elsie Janis, Nance O'Neil, and Alla Nazimova, whose intimate female liaisons were variously interpreted around the turn of the century; the "lavender marriages" of Alfred Lunt to Lynne Fontanne and Guthrie McClintic to Katharine Cornell; the lesbian collaborations of Margaret Webster and Cheryl Crawford; the comic antics of Monty Woolley, which negotiated codified constructions of homosexual perversion in the post-Freudian interwar years; and the on- and offstage performances of Mary Martin and Joe Cino, which resisted the paranoid enforcements of heterosexual normality in the McCarthy era. Central to these investigations are the complex connections of performances of sexuality and gender and their different implications for men and women practitioners working under pervasive sexism and homophobia.